2022
DOI: 10.3390/molecules27123813
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Study and Antiglioblastoma Activity Assessment of Plectranthus hadiensis (Forssk.) Schweinf. ex Sprenger var. hadiensis Stems

Abstract: Glioblastoma (GB) is the most malignant form of primary astrocytoma, accounting for more than 60% of all brain tumors in adults. Nowadays, due to the development of multidrug resistance causing relapses to the current treatments and the development of severe side effects resulting in reduced survival rates, new therapeutic approaches are needed. The genus Plectranthus belongs to the Lamiaceae family and is known to be rich in abietane-type diterpenes, which possess antitumor activity. Specifically, P. hadiensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 50 publications
2
19
1
Order By: Relevance
“…All PHT extracts showed antimicrobial activity against both Gram-positive and Gramnegative bacteria, which differs from previous reports [10,37,44,45] where PHT extracts exhibited antimicrobial activity only against Gram-positive bacteria such as Staphylococcus aureus, Bacillus subtilis, Micrococcus flavus, and Enterococcus faecalis. However, Kotagiri, Shaik, and Kolluru [8], as well as Sripathi and Ravi [46], reported that in addition to having antimicrobial activity against Gram-positive bacteria, PHT extracts also showed activity against Gram-negative bacteria such as Escherichia coli and Pseudomonas aeruginosa.…”
Section: Antimicrobial Activity Of the Extractscontrasting
confidence: 99%
See 1 more Smart Citation
“…All PHT extracts showed antimicrobial activity against both Gram-positive and Gramnegative bacteria, which differs from previous reports [10,37,44,45] where PHT extracts exhibited antimicrobial activity only against Gram-positive bacteria such as Staphylococcus aureus, Bacillus subtilis, Micrococcus flavus, and Enterococcus faecalis. However, Kotagiri, Shaik, and Kolluru [8], as well as Sripathi and Ravi [46], reported that in addition to having antimicrobial activity against Gram-positive bacteria, PHT extracts also showed activity against Gram-negative bacteria such as Escherichia coli and Pseudomonas aeruginosa.…”
Section: Antimicrobial Activity Of the Extractscontrasting
confidence: 99%
“…tomentosus (PHT) or "VapoRub TM plant", as it is commonly called in Mexico, it has been used to treat various digestive, respiratory, and skin problems, such as dysentery, 2 of 19 vomiting, nausea, diarrhea, fever, sore throat, common cold, asthma, inflammations, and smallpox, because it is a rich source of bioactive phytochemicals, especially terpenoids. The juice from the leaves and stems mixed with honey treats diarrhea, while its infusions treat cough [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), this adult-type diffuse glioma is classified as a grade IV tumor (highly malignancy level) [ 1 ]. Despite the advances in the clinic to improve patient survival, the overall average survival rate for GB is only 15–21 months after diagnosis, with just a 5% probability of survival in the 5 years post-diagnosis [ 2 , 3 , 4 ]. These numbers are not surprising, being explained by the late diagnosis and poor prognosis of GB.…”
Section: Introductionmentioning
confidence: 99%
“…These numbers are not surprising, being explained by the late diagnosis and poor prognosis of GB. Thus, to hinder this situation, the current first-line treatment available for GB includes maximal surgical resection followed by concomitant cycles of chemoradiotherapy and adjuvant chemotherapy (temozolomide (TMZ)) [ 3 , 4 , 5 , 6 , 7 ]. Although, these treatments have several limitations, such as incomplete surgical resection or development of multidrug resistance (MDR), that provoke patient relapse [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation